Algebraic coding techniques for error detection in data transmission / Nasaruddin Zenon - Zenon, Nasaruddin (Universiti Teknologi MARA Cawangan Pahang, 1989)
The purpose of this paper is to describe currently available algebraic coding techniques for error detection in computer communication and the problems associated with them. We will first discuss the simplest technique being employed followed by complicated ones involving cyclic codes. We will also introduce a simple comparison method for information flow rate in data transmission. This method can be used to compare all (n, k) - codes with a fixed error rate.